A matrix representation for the verification of separability of robustness diagrams with loop and time controls - Amancio, Joenne Mied G.
Modularization of workflows provide foundations of good system maintenance, scalability, evolution, and a means to identify sequential and parallelizable profiles of systems that these workflows represent. In this research, we focus on a multidimensional workflow called the Robustness Diagram with Loop and Time Controls (or RDLT) and its model property known as separability. Separability, in the context of RDLT, pertains to its characteristic of having maximal substructures where each can work in their full capacities and intentions without impeding other substructures despite the existence of shared resources and volatile components. To date, there is still no literature that provides algebraic representations and relevant strategies in aid of efficient and automatable verification of separability. Through this research, we propose matrix-based representations and relevant algorithms for such verification as inspired from graph-based techniques in literature. Thereafter, we prove the correctness of our proposed algorithms, their time and space and complexities, and finally report our experimental results.